Does it Pay to Work for Free? Negative Selection and the Wage Returns to Volunteer Experience. (2nd May 2017) - Cozzi, Guido; Mantovan, Noemi; Sauer, Robert M.
Abstract: This paper offers the first instrumental variables estimates of the wage returns to volunteer experience. The returns are substantial and differ considerably by gender. The results imply that the unequal valuation of volunteer experience by gender is more important in explaining the gender earnings gap than is the unequal valuation of part‐time paid work experience. The results also indicate negative selection into unpaid work. In a simple model of optimal volunteering, negative selection implies that a lower cost of volunteering would produce both an expanded and higher‐skilled pool of volunteers, and greater societal benefits from volunteer work.